Leaf Fermentation Products of Allium sativum L. Can Alleviate Apple Replant Disease (ARD) - Chengwen Yin; Rong Zhang; Yiming Zhao; Gongshuai Wang; Chengmiao Yin; Yusong Liu; Zhiquan Mao (Horticulturae, 2024)
Apple replant disease (ARD) is a serious threat to newly replanted apple seedlings. The alleviation of ARD is of great significance for the healthy development of the apple industry. In this study, we investigated the effects of leaf fermentation products (LFP) of Allium sativum L. on the replanted soil environment and Malus hupehensis Rehd. seedlings. The results showed that LFP increased biomass accumulation, changed root architecture, increased root anti-oxidant enzyme activity, and decreased root MDA content under replanted conditions. In addition, the application of LFP increased soil nutrients and soil enzyme activity and reduced phenolic acid content. Furthermore, the LFP enriched the number of beneficial bacteria and reduced the number of harmful fungi, which positively affected the soil microbial community structure. Overall, our results demonstrated that LFP of A. sativum L. could alleviate the occurrence of ARD and provide new insights for the reuse of the leaves of A. sativum L. and the prevention of ARD.